Implementation of Learning Supervision by The Head of Madrasah in Efforts to Increase Teacher Performance - Samiyah Samiyah (AT-TURATS, 2021)
This study reveals the implementation of learning supervision by the madrasah principal in an effort to improve teacher performance at MTS Negeri Siantan. To get maximum results, this research focuses on: 1). How is the learning supervision plan carried out by the head of MTSN Siantan in improving the performance of PAI teachers? 2). How is the implementation of learning supervision carried out by the head of MTSN Siantan in improving the performance of PAI teachers? 3). How is the evaluation of learning supervision carried out by the principal of MTSN Siantan in improving the performance of PAI teachers? 4). How is the follow-up learning supervision carried out by the principal of MTSN Siantan in improving the performance of PAI teachers? This study uses a qualitative approach with data collection methods documentation and interviews. This study concludes that: 1). The planning for supervision of learning by the madrasa head in improving the performance of PAI teachers at MTs Negeri Siantan has been well planned; 2). The implementation of learning supervision by the madrasah principal in improving the performance of PAI teachers has been carried out well. However, it needs to be improved so that the implementation is more perfect in order to improve teacher performance; 3). The evaluation of learning supervision by the madrasah principal has been carried out well; 4). Follow-up supervision of learning by the principal in improving the performance of PAI teachers has been carried out well.